Microwave-assisted drying of clay roof tiles. Issue 9 (12th July 2022) - Briest, L.; Wagner, R.; Tretau, A.; Tsotsas, E.; Vorhauer-Huget, N.
Abstract: Following the successful drying experiments conducted with a domestic microwave oven, this study presents the results of laboratory scale drying of clay tiles. The drying process was realized as a combination of convective drying with microwave heating. In detail, the dependence of drying time and total energy consumption on process conditions were investigated. For this analysis, the microwave power was either intermittently supplied or continuously increased with a ramp profile during the microwave heating periods. Additionally, the impact of the drying air temperature was investigated. The scale-up from the basic experiments to the lab scale plant was realized by successive increase of the sample size. Process control was based on temperature measurement of the drying sample. The results suggest intermittent microwave heating as an alternative option for fast and sound drying of clay roof tiles. Increase of air temperature instead had a minor impact on drying indices. In comparison with continuous heating, the major advantages of intermittent heat supply are its energy efficiency and the better options for process control.